2009
DOI: 10.2135/cropsci2008.07.0402
|View full text |Cite|
|
Sign up to set email alerts
|

Bahiagrass Tetraploid Germplasm: Reproductive and Agronomic Characterization of Segregating Progeny

Abstract: The tetraploid germplasm of bahiagrass, Paspalum notatum Flüggé, is an unexploited source of variability that can be used for the genetic improvement of this species as forage or turf. The objectives of this research were to develop a segregating population by hybridizing induced sexual and apomictic clones and to characterize the resulting population for mode of reproduction, seed fertility, growth habit, seasonal growth pattern, and frost resistance. A population of 591 hybrids had a 4:1 ratio between sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
76
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 17 publications
5
76
0
Order By: Relevance
“…In fact, the use of apomixis is currently having direct consequences on the breeding of natural apomictic forage grasses of the Brachiaria [9–11] and Paspalum [12, 13] genera, allowing a significant increase in cattle production in tropical and sub-tropical areas of the Americas. However, major food crops such as maize, rice and wheat are not naturally apomictic and attempts to introduce the trait from wild relatives remain unsuccessful as yet [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the use of apomixis is currently having direct consequences on the breeding of natural apomictic forage grasses of the Brachiaria [9–11] and Paspalum [12, 13] genera, allowing a significant increase in cattle production in tropical and sub-tropical areas of the Americas. However, major food crops such as maize, rice and wheat are not naturally apomictic and attempts to introduce the trait from wild relatives remain unsuccessful as yet [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…In "bahiagrass", apomixis is aposporic and pseudogamous, in which embryo sac arises by mitotic division of a somatic cell of the embryo sac and endosperm develops by the union of a male nucleus of the pollen grain with the polar nuclei (Acuña et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this manner, they are able to reinitiate growth faster at the beginning of the warm season, thus decreasing the forage deficit period (COSTA et al, 2003). ACUÑA et al (2009) observed that the hybrids of P. notatum that showed greater TCold also demonstrated a greater capacity for re-growth. When considering all the forage traits of interest, the results demonstrated that although the tested progenies did not surpass the Azulão genotype in TDM production, the hybrids 08Q01 and 08Q44 stand out, particularly in production of LDM and TCold.…”
Section: ------------------------------------------------------------mentioning
confidence: 93%
“…In each cut, it was counted the number of tillers (NT). Plant height (PH, cm plant -1 ) was measured from the soil to the average bending height of leaves in the canopy, whereas the plant coverage diameter (PCD, cm planta -1 ) was estimated using the average coverage diameter for each plant (ACUÑA et al, 2009;PEREIRA, 2013). Approximately five days after each cut, visual notes were made concerning new sprouts using a scale from 1 to 5, with 1 denoting lower re-growth ability and 5 indicating the best (PEREIRA, 2013).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation